Evaluation of Reconstructions of Snow/Ice Melt in Greenland by Regional Atmospheric Climate Models Using Laser Altimetry Data. Issue 16 (24th August 2018) - Sutterley, Tyler C.; Velicogna, Isabella; Fettweis, Xavier; Rignot, Eric; Noël, Brice; van den Broeke, Michiel
Abstract: The surface mass balance of the Greenland ice sheet critically depends on the intensity of ice melt/snowmelt in its ablation zone, but in situ data have been too limited to quantify the error of regional climate models. Here we use 23 years of NASA satellite and airborne laser altimetry from the Airborne Topographic Mapper; Land, Vegetation, and Ice Sensor; and Ice, Cloud, and land Elevation Satellite to generate time series of elevation change to compare with surface mass balance products from the Regional Atmospheric Climate Model and from the Modèle Atmosphérique Régional. For 1994–2016, the results agree at the 15–26% level, with the largest discrepancy in North Greenland. During the cold summer of 2015, the root‐mean‐square discrepancy is 40% in the north, 30% in the southwest, and 18–25% at low elevation. The difference drops to 23% in the southwest and 14% at low elevation during the 2016 warm summer. Plain Language Summary: Snowelt/ice melt is a major component of the mass loss of the Greenland ice sheet and its contribution to global sea level rise. Here we evaluate the accuracy of regional atmospheric climate models at reconstructing ice melt/snowmelt in Greenland for the first time using 23 years of thousands of kilometers of laser altimetry data. Such study was not possible in the past due to a lack of long‐term, geographically diverse, in situ data. We find that the regional climate models track down the long‐term trend in snowmelt/ice melt with remarkable accuracy across Greenland and do very well in warm summers, but we caution that model performance degrades at the regional level, for example, in North Greenland. Key Points: We assess the accuracy of reconstructed runoff from regional climate models, a dominant control on the Greenland ice sheet mass balance Time series of mass changes from 23 years of altimetry and seasonal data indicate that the error in runoff is at the 20% level Airborne laser altimetry provides orders of magnitude more data for regional climate model assessment than available in situ